Netralitas Aparatur Sipil Negara Dalam Pemilihan Kepala Daerah Di Maluku - Pattiruhu, Christian; Singkery, Michael Rolando (Jurnal Saniri, 2024)
This study examines the neutrality of the State Civil Apparatus (ASN) in the context of local elections (Pilkada) in Maluku, Indonesia. Article 2 of Law No. 5 of 2014 on ASN stipulates that the implementation of ASN policies and management should be based on the principle of neutrality. Bureaucratic neutrality is a system where the quality of public service delivery remains consistent regardless of changes in leadership. This research explores the critical role of ASN neutrality in maintaining the integrity of public services and democratic processes. The study emphasizes the importance of ASN remaining impartial and free from political interventions, particularly during local elections. In the context of Pilkada in Maluku, this research investigates how ASN maintains distance from all political forces and refrains from practices of intimidation or threats towards other ASN employees and the public. The findings highlight the challenges and strategies in upholding ASN neutrality, contributing to the broader discourse on bureaucratic professionalism and the quality of local democracy in Indonesia. This study provides valuable insights for policymakers and practitioners in enhancing the neutrality and integrity of civil servants in the political landscape of Maluku and beyond.